2013
DOI: 10.1111/ijfs.12171
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of frozen storage‐induced oxidation and structural changes in myofibril of common carp (Cyprinus carpio) surimi by cryoprotectant and hydrolysed whey protein addition

Abstract: Summary The objective of the present study was to evaluate the efficacy of combined cryoprotectants (sucrose + sorbitol) and whey protein isolate (WPI) hydrolysates to inhibit protein oxidation and quality loss in common carp (Cyprinus carpio) surimi during frozen storage at −25 °C. With increasing storage time, the carbonyl content of myofibrillar proteins increased from 4.02 nmolmg‐1 protein (0 day) to 7.25, 6.31, 5.26 and 4.83 nmol mg−1 protein (180 days; P < 0.05) for the control and samples with cryoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 40 publications
(54 reference statements)
3
22
0
Order By: Relevance
“…Benjakul and Sutthipan [6] reported an increase in the SoANS of natural actomyosin extracted from crab muscle during 8 weeks of frozen storage. e increase in surface hydrophobicity of frozen the Basa fillet was in agreement with other studies that showed an increased surface hydrophobicity as frozen storage time increased [4,34]. In addition, some studies also revealed that the increased protein oxidation, such as increasing of surface hydrophobicity, was coincidental with the increased lipid oxidation [35,36], suggesting that protein structural changes might be a result of the reaction between functional groups of proteins and oxidation products of polyunsaturated fatty acids [37].…”
Section: Changes In Surface Hydrophobicitysupporting
confidence: 89%
See 1 more Smart Citation
“…Benjakul and Sutthipan [6] reported an increase in the SoANS of natural actomyosin extracted from crab muscle during 8 weeks of frozen storage. e increase in surface hydrophobicity of frozen the Basa fillet was in agreement with other studies that showed an increased surface hydrophobicity as frozen storage time increased [4,34]. In addition, some studies also revealed that the increased protein oxidation, such as increasing of surface hydrophobicity, was coincidental with the increased lipid oxidation [35,36], suggesting that protein structural changes might be a result of the reaction between functional groups of proteins and oxidation products of polyunsaturated fatty acids [37].…”
Section: Changes In Surface Hydrophobicitysupporting
confidence: 89%
“…Conversion of sulfhydryl groups into disulfides and other oxidized species can be due to radicalmediated oxidation of protein [39]. Decreases in sulfhydryl group content of common carp (Cyprinus carpio) surimi as influenced by frozen storage have been reported [34].…”
Section: Changes In Sulfhydryl Group and Disulfide Bondmentioning
confidence: 99%
“…However, intramolecular conformational changes and subsequent intermolecular aggregation of myosin and actomyosin (AM) are inevitable during freezing and frozen storage; thereby, decreases in gelation properties and water‐holding capacity (WHC) occur (Li et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Surimi is usually frozen to alleviate the deterioration caused by microorganisms before processing into surimi products. However, intramolecular conformational changes and subsequent intermolecular aggregation of myosin and actomyosin (AM) are inevitable during freezing and frozen storage; thereby, decreases in gelation properties and water-holding capacity (WHC) occur (Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of sulfhydryl groups into disulfides and other oxidized species can be due to radical-mediated oxidation of protein (Dean, 1997). Decreasing sulfhydryl group content of common carp (Cyprinus carpio) surimi as influenced by frozen storage and multiple freeze-thaw cycles has been reported Li et al, 2013). Polymerization of high molecular weight protein via disulfide bonding in fish muscle induced by iron was also reported (Tokur et al, 2007).…”
Section: Changes In Sulfhydryl and Disulfide Bond Contentsmentioning
confidence: 99%